Pengaruh Penghargaan dan Pengembangan Karir Terhadap Penilaian Kinerja Pekerja (Studi Penelitian Pada Karyawan Generasi Milenial di Jawa Barat) - Intan Rahmadhani; Eman Sulaeman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to: (1) examine the effect of career development and rewards on employee performance. (2) to examine the effect of career development on worker performance. (3) to examine the effect of rewards on worker performance. This study uses a research method that is multiple linear regression analysis. The population and sample used by researchers is a sample of 48 permanent workers. The sampling technique uses saturated sampling technique where all members of the population are used as samples. The results of the study show that career advancement and rewards have a positive and significant effect on the performance of public relations workers. The career development variable has a positive and significant effect on employee performance. The reward variable has a positive and significant effect on worker performance. That means, the higher the career development and rewards in later life, the better are the two variables that affect performance in the industry. For future researchers, it is suggested to develop other factors that affect performance beyond the factors that have been studied, for example work motivation, work environment, work discipline, or anything that can make a high contribution in improving worker performance in the field.